ASSESSMENT OF SOCIO-ECONOMIC DEVELOPMENT OF THE SUBJECTS OF THE RUSSIAN FEDERATION - E. Mamleeva; N. Trofimova; M. Sazykina (Вестник Северо-Кавказского федерального университета)
In order to develop an effective regional policy and reduce the asymmetry in the development of the subjects of the Russian Federation, a comprehensive multidimensional assessment of the ongoing processes in the economic and social spheres is necessary. The article presents the results of assessing the level of socioeconomic development of the regions of the Russian Federation in 2014 and 2019. The proposed approach to analysis is based on the construction of indexes by blocks reflecting the most important aspects of the social and economic development of territories. The data obtained made it possible to form cartographic profiles of subjects for monitoring the functioning of the economic and social spheres of the regions. The analysis carried out will allow using a targeted approach in the development of state regional policy.